Avaliação de dieta alto grão e da inclusão de óleo residual de fritura na alimentação de cordeiros - Batista, Nayane Valente (2020)
The objective was to evaluate the effect of high grain diet and diet with the inclusion of 6% of frying oil on performance, carcass characteristics, meat quality and production costs of confined lambs. Control and with with residual frying oil diets were balanced for gain of 200g daily (NRC 2007), maintaining the bulky:concentrated in the ratio 40:60, and the high grain diet consisted of commercial bran concentrate used on finishing in sheep. Fifteen crossbreed Dorper x Santa Inês lambs from were used, six-month-old, confined and distributed in a completely randomized design (DIC). After 40 days of confinement, the animals were slaughtered. There was no statistical difference (P> 0.05) between the control diets and with residual frying oil, expressed in grams / day (g/day) and percentage of live weight (% PV) for daily consumption of dry matter (CMS), crude protein (CPB), mineral matter (CMM), neutral detergent insoluble fiber (CFDN) and total carbohydrates (CCT), with the lowest averages for these variables being observed with the high grain diet. The highest averages for final weight (PF), total weight gain (GPT) and daily weight gain (GPD) were observed with the control diets and with the inclusion of residual oil, which did not differ between them (P> 0.05) . There was no effect (P> 0.05) of treatments on hot carcass (RCQ), cold carcass (RCF) and true (RV) yields. The physical parameters of the meat (P> 0.05) were not influenced by the diets. The values of crude protein and meat lipids were higher for treatment with 6% residual oil, not differing (P> 0.05) for these parameters of the control diet. Regarding the moisture content, the meat of the animals of the high grain diet was superior and statistically different (P <0.05) from the other treatments. Higher carcass weight and additional profit per animal were obtained in the diet with the inclusion of residual frying oil, observing negative values with the high grain diet for these economic indicators. The use of diet with 6% of residual frying oil proved to be advantageous from a productive and economic point of view, by providing better productive performance, without altering the physical and chemical characteristics of the meat.